The influence of human resource empowerment, work commitment, and organizational culture on employee performance at PT. Ihsanindo sukses makmur - Noviyadi, Noviyadi; Tussi Sulistyowati; Wasiman, Wasiman (Jurnal Ekonomi, 2024)
The primary objective of this research is to scrutinize the influence of Human Resource Empowerment, Work Commitment, and Organizational Culture on employee performance at PT Ihsanindo Sukses Makmur in Batam. Employing multilinear regression analysis with SPSS 27, the study aims to furnish comprehensive insights into both the individual and collective impacts of these factors. Employing a quantitative approach, the research includes a population of 288 employees, and a sample of 167 respondents chosen through the Slovin formula and random sampling. The aim is to yield statistically significant findings, supported by key metrics such as regression coefficients, t-test results, and an F-test value. The overarching goal is to contribute to a profound understanding of the intricate dynamics shaping colleague performance within the organizational context. The subsequent findings uncover substantial and independent impacts of Human Resource Empowerment, Work Commitment, and Organizational Culture on employee performance. These variables collectively exert a robust and statistically significant influence on performance, highlighted by a calculated regression coefficient of 7.107 and an F-test value of 149.301, surpassing the tabulated threshold. The acceptance of study hypotheses underscores a substantial and positive relationship between these factors and employee performance at PT Ihsanindo Sukses Makmur.